1963
DOI: 10.1542/peds.32.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Masses in Infants and Children

Abstract: Two hundred sixty-seven patients with tumors in the neck, observed at the Children's Memorial Hospital, have been reviewed. Forty-seven of these patients had malignancy. The most common malignancy was lymphosancoma or Hodgkin's disease (20 cases). The highest incidence of malignant degeneration in tumors of a specific organ occurred in the thyroid (50%). The over-all malignancy rate in neck tumors in this series was 15.7%. This study was undertaken primarily to evaluate clinical patterns and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…All variables used in our diagnostic model, besides TARC, have been described previously as separate predicting factors for lymphoma [8,32,33,37,[46][47][48][49][50][51][56][57][58][59][60][61]. Our study confirmed that enlarged mediastinum is an absolute "red flag", calling for prompt referral to the pediatric oncologist.…”
Section: Discussionsupporting
confidence: 78%
“…All variables used in our diagnostic model, besides TARC, have been described previously as separate predicting factors for lymphoma [8,32,33,37,[46][47][48][49][50][51][56][57][58][59][60][61]. Our study confirmed that enlarged mediastinum is an absolute "red flag", calling for prompt referral to the pediatric oncologist.…”
Section: Discussionsupporting
confidence: 78%
“…It never involves skin and it shows positive transillumination test. The common location of cystic hygroma is in the anterior and posterior triangles of the neck, with the posterior triangle of the neck being the most common site of occurrence [19] . Some of the cystic hygromas present with large neck masses with obstructive symptoms such as dysphagia or adult respiratory distress if they are located in the suprahyoid region, and these lesions are associated with a higher rate of recurrence, complications, and morbidity [20] .…”
Section: Discussionmentioning
confidence: 99%